Reducing food losses and improving the quality of locally produced spinach - Batziakas, Konstantinos (Kansas State University, 2019)
Food loss and waste (FLW) constitute a substantial problem for global food security. Particularly, fresh produce constitutes 44% (by weight) of the global FLW. FLW of fresh produce occurs throughout the food chain, from production to the consumer. In the Central U.S., many small-acreage fruit and vegetable growers are utilizing high tunnels, which have been successful at increasing the yield of several crops. However, little is known about the effect of this production system on FLW. Moreover, small acreage producers have limited access to postharvest handling resources like refrigeration, which can lead to FLW during storage. Finally, consumer dissatisfaction is one of the main drivers of postharvest food waste in fresh produce. The overall objective of this dissertation was to investigate interventions for reducing FLW of locally produced spinach (Spinacia oleracea cv. Corvair). The effect of the high tunnel production system on preharvest losses, quality at harvest and during storage, consumer acceptability, and shelf life of spinach were examined and compared to the open field production system. We also evaluated the effect of passive Modified Atmosphere Packaging (MAP) on the quality and shelf life of locally grown spinach stored at non-optimum temperatures of 13 and 21 °C. Field experiments were carried out at the Kansas State University Olathe Horticulture Center from 2014 to 2017. We utilized a systems approach with six replications for each growing system. Shelf life experiments were performed at near-optimum and non-optimum temperatures. Spinach produced in high tunnels consistently demonstrated significantly higher marketable yield and higher percent marketability when compared to spinach produced in the open field. Both production systems produce spinach of premium physical and nutritional quality. There were no differences between the two treatments when spinach was stored at 3 °C. However, high tunnel spinach demonstrated improved postharvest behavior at 13 °C due to reduced respiration and yellowing rate and increased water content when compared to the open field. Consumer acceptability and sensory characteristics of spinach grown in the two systems were evaluated using a consumer study and descriptive sensory analysis. Consumers preferred spinach produced in high tunnels in terms of overall liking, flavor liking, and texture liking when compared to the open field and non-local spinach. Descriptive analysis showed that locally grown spinach had a higher intensity of attributes that indicate premium quality, such as green color and green/spinach flavors. BreatheWay® technology was investigated for the passive MAP experiments and spinach was stored at non-optimum temperatures. Spinach stored in MAP demonstrated a storage life extension, due to a slower rate of yellowing and water loss. The results of this work indicate that high tunnel production can reduce the FLW of spinach and produce a crop of high organoleptic quality that is preferred by consumers. Passive MAP has the potential to extend the storage life and maintain the quality of spinach stored at non-optimum temperatures. FLW is a complex challenge for the global food system and its reduction requires multidisciplinary collaboration, innovation and an approach tailored to the specificities of the various food chains.
Keywords: Spinach; Local food; Food losses; Postharvest; High tunnels; Food security